Upaya Adaptasi Pedagang Kaki Lima Kawasan Malioboro di Tengah Pandemi Covid-19 - Igor Eris; Sudaryono Sastrosasmito (REKA RUANG, 2021)
COVID-19 pandemic which spreading rapidly to the entire area on earth have huge impact on all sectors, notably on tourism that rely on people’s mobility and tourists visit number. Lost of tourist visit in tourism area lead to people’s income fall into a tailspin especially on people who work on tourism sector, including street vendors in Malioboro. Direct impact that preceived by the street vendors in Malioboro are their daily income decreased significantly and needed to find strategies in order to survive. Survival strategies which practiced by the streets vendor consist of selling as usual without any special strategy, attracting more buyers by increasing their commodities appeal, seeking for buyers outside of Malioboro, having other jobs outside of selling goods in Malioboro, and street vendors that operate in the evening, they re-arrange their operational hour during PTKM.